Patient experiences of UK ambulance service telephone triage: a review of the literature. Issue 2 (27th November 2019) - Brady, Mike
Abstract : Purpose: Telephone triage or hear and treat (H&T) describes the process of UK ambulance services nurses and paramedics undertaking enhanced telephone assessments of patients to determine the most appropriate response, which can sometimes result in no ambulance being sent. Given, however, that 999 is not considered an advice service, it may be reasonable to assert that the expectation of those calling 999 is always an immediate ambulance response. This may not always be realised and may affect patient experience. The purpose of this paper is to ascertain the following: to what extent are the views of UK ambulance telephone triage service users being gathered? In answering this research question, this review also aims to explore the findings to determine service users' expectations of ambulance telephone triage and the possibility that these expectations are influenced by the UK media. The findings of which could be used to inform the need and nature of future research. Design/methodology/approach: Phase one consisted of a computerised literature search of online databases CINAHL, Pubmed, Science Direct, Cochrane library, Web of Science and UK government-funded databases. Phase two consisted of searches of all UK ambulance services websites and the submission of freedom of information requests. Phase three consisted of a computerised literature search of the ProQuest international news-stream database. Findings: A total of 78 results were identified and after further screening 34 results were excluded, leaving 44 for final review. The extent to which users experience of ambulance service telephone triage are being gathered is low; and often limited to one off pieces of non-peer reviewed work. Patients felt overall that they were treated with respect, dignity and care. However, being listened to, reducing anxiety and a need for prompt assurances remain important to those whose overriding expectation is that an ambulance should attend every time a 999 call is made. There appears to be a balanced media portrayal of H&T with the UK media. However, unrealistic public expectations represent a significant barrier to providing sustainable care that users consider to be of high quality. Research limitations/implications: Some user experiences may have been gathered in more broad research exercises which explored various aspects of 999 ambulance service experience. This was not included if it could not be clearly differentiated as being related to H&T and thus may have resulted in data being omitted. It was not possible to systematically search social media platforms (such as facebook or twitter) for any media results related to this search strategy; only traditional print and online media platforms. This also may have resulted in data being omitted. The inclusion of non-peer reviewed research results and grey literature represents a possible limitation to the conclusions drawn within this review. The concept of Insider Research Bias cannot be ignored within this review. The author himself practices in telephone triage within a UK ambulance service; however, this insider bias is mitigated by the clearly articulated systematic methodology and use of the Critical Appraisal Skills framework. In a similar vein, reviews of this nature are also often conducted as part of a team, to reduce bias, increase objectivity and ensure the validity of findings. This review was a sole effort, and while this is not uncommon, there were no cross checks by peers of the search terms, strategy, paper selection, exclusion criteria or data extraction. This lack of peer critique is considered a possible limitation in mitigating selection and reviewer bias. Practical implications: The results of this review would suggest a need to increase the amount of research and patient feedback gathered from those being assessed and managed by ambulance service telephone triage within the UK. Ambulance services could hold regular monthly small-scale qualitative interviews with patients and families to ascertain their views, perceptions and anxieties which can then provide an up-to-date understanding of user expectations and the health educational needs of local communities. Patient feedback received directly to ambulance services or via the Patient Advice and Liaison Service could be retrospectively analysed by researchers to determine key themes of positive practice or negative patient experience. Such feedback can be tracked through time and be used as a pre and post community intervention measure, to determine any changes. Moving forward, nationally standardised research frameworks should be adopted to provide more easily collated local and national data, which can monitor improvement strategies and provide a comparison between services to aid the sharing of best practice principles. Originality/value: There is no other piece of work published which has reviewed the data in this area of clinical practice within the UK.